The America First energy policy of the Trump Administration. Issue 3 (3rd July 2017) - Anderson, Scot; Biever, Jennifer; Desai, Sachin; Downey, Kevin; Gutierrez, Ana; Hellreich, Allison; Krantz, Stefan; Launer, Zack; Lillie, Andrew; Lilyestrom, John; Ratliff, Dale; Roma, Amy; et al.
Abstract : At the time of writing, the Trump Administration is nascent, in existence for less than ten weeks. During that short time, however, the President has made it abundantly clear that he intends to occupy his new office in the same way he ran his presidential campaign – loudly, caustically and with a single-minded vision bent on turning government and United States policy upside down, ostensibly to benefit American citizens, American workers and American business. Although many commentators have said that this broad-brushed approach to governance overemphasises bold results over thoughtful process and idealism over nuance, thereby ignoring or otherwise casting aside important details, no one should be the least bit surprised that it's happening.